Performance of Integrated Healthcare Center Cadre and Scope of Community Participation - Zaki Irwan; Faturrahman Faturrahman; Irma Muslimin (GLOBAL HEALTH SCIENCE GROUP, 2019)
Integrated Healthcare Center is one of the social institutions that play a role in the approach of community participation in the health sector. Integrated Healthcare Center serves as a real entrance to all basic health services especially for infants, toddlers, and pregnant women. This study aims to assess the performance of Integrated Healthcare Center cadres and the scope of community participation in Pangali-Ali Village, Banggae District, Majene Regency 2016. This research was conducted with analytical methods with cross-sectional approach to assess the performance of Integrated Healthcare Center cadres and the scope of community participation in Pangali-Ali Village, Banggae District, Majene District. This research was conducted at Integrated Healthcare Center Village Pangali-Ali Banggae District Majenen Regency, a total sample of 400 mothers who have children under five. The results of research on community participation in Integrated Healthcare Center services on the growth of children under five in Pangali-Ali Village Majene Regency, West Sulawesi Province) that the Integrated Healthcare Center cadre performance in the five-table system at the Integrated Healthcare Center in Pangali-Ali village is categorized as good, only for counseling (table IV) there are things that are lacking effective in particular the provision of information and counseling by cadres is still not in accordance with maternal expectations. Keywords: performance, cadre, integrated healthcare center